UNDERSTANDING THE STATE CIVIL APPARATUS’ NEUTRALITY IN GENERAL ELECTIONS FROM THE DIGNIFIED JUSTICE JURISPRUDENCE PERSPECTIVE - Kameo, Jeferson; Prasetyo, Teguh (UNISSULA, 2024)
The fundamental issue in every general election, for instance the Indonesia’s 2024 election, is the existence of stipulated principle of neutrality of the State Civil Apparatus (SCA) in election laws. The principle has been in conflict with the highest values which should govern it. The purpose of this research is to describe and discuss the idea or effective legal theory for solving the conflict of SCA with the highest values that should govern it. The research applied the Indonesian legal theory known as Dignified Justice to navigate the finding. The methods used is pure legal research or the normative legal research. It has found that the root problem of violations of the principle of SCA in, for instance the 2024 is that election laws is in conflict with the Pancasila, which has long been understood as not as the highest law, but an ideology, while an ideology has been argued as a manipulative tool of a ruling elite to control its subject. In order to solve the problem, this study proposes that Pancasila should be treated as containing the highest values or the inner morality of law to govern the principle of SCA stated in the country’s election laws.